Cryopreservation of Simmental cattle semen with egg yolk from different avian species and level glycerol of different in tris diluent - Yendraliza Yendraliza; Yudi Gusti Rahman (Livestock and Animal Research, 2023)
Objective: This research was conducted to determine the effect of egg yolk from different avian species and the level glycerol of different in maintaining sperm quality in Simmental cattle in tris diluent.Methods: Semen comes from Simmental (n=3) kept at the Tuah Sakato Artificial Insemination Center (BIB), Payakumbuh, West Sumatra. The diluent used in this research was tris egg yolk derived from three types of egg yolk (Factor A; the egg yolks used to come from ducks, quails and chickens) and different doses of glycerol (Factor B; 6, 6.5 and 7%). The research method used was a Randomized Block Design (RBD) with 2 factors. The shelter sperm is a group. The variables observed were the percentage of motility, abnormality, percentage of live sperm and intact plasma membrane of Simmental cattle sperm after thawing.Results: The results showed no interaction between glycerol levels with types of egg yolk in tris extender of Simmental sperm quality. The tris diluent with duck egg yolk was better than chicken egg yolk which was equivalent which was able to motility up to 52.67%, percentage of live sperm was 70.78, abnormal sperm was only 14.44% and IPM was up to 42.44%. The dose of glycerol 6 ml is better than 6.5 ml and 7 ml resulting in motility up to 52.44%, live percentage reaching 70.22%, abnormal sperm at 14.33% and IPM up to 43%.Conclusion: The use of duck egg yolk in tris extender and the addition of 6% glycerol resulted in better sperm quality in Simmental cattle with high motility, percentage of live sperm, IPM and lower abnormal sperm.